Prediction Orientation: The Role of Good School Governance and Internal Control Systems in Moderating the Influence Between Proactive Fraud Audits on Fraud Prevention - Irwan Christatnto Edy; Shandy Marsono; Setyani Sri Haryanti (Asosiasi Dosen Akuntansi Indonesia, 2022)
The study aims to test predictive models about the effect of proactive fraud audits on fraud prevention moderated by internal control systems and good school governance. The research was conducted with the object of employees managing school operational assistance (BOS) funds at Wonogiri High School Indonesia. Method of data collection by purposive sampling. Data retrieval techniques with questionnaires. Data analysis with SEM-PLS. The results found that 1) Proactive Fraud Audit negatively affects fraud prevention, 2) Internal control systems moderate negative influences on the connectedness between proactive fraud audit to fraud prevention, 3) Good school governance moderates positive influence on the connectedness between proactive fraud audit to fraud prevention. The findings of this study provide practical benefits for schools to minimize fraud efforts in bos fund management